PERILESIONAL INFILTRATION OF GLUCANTIME AND LIDOCAINE FOR TREATMENT OF LEISHMANIASIS - Reyes Alirio Torres; Nieves Vargas de Caminos (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2000)
In order to evaluate the therapeutic effect of perilesional infiltration of a mixture of Glucantime and lidocaine in localized cutaneous leishmaniasis, 165 patients with different clinical forms of the disease were selected, from the Dermatology Services of the Central Hospital "Antonio María Pineda "From Barquisimeto and the University Hospital of Maracaibo. Complete healing of the lesions was observed in 100% (128 of 128) of the patients treated with the Glucantime and lidocaine mixture, in 71.4% (20 of 28) of those treated only with Glucantime and only 11.1% (1 of 9) of those who received lidocaine alone. In 65.6% 4 of the cases healing occurred with 3 to 10 infiltrations and in 34.4% 11 to 18 doses were necessary. Standardization of the management and registration of leishmaniasis is suggested and treatment of localized forms with perilesional infiltrations of Glucantime plus lidocaine is recommended.